2020
DOI: 10.1002/fsn3.1705
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐based proteinaceous snacks: Effect of fermentation and ultrasonication on end‐product characteristics

Abstract: The study aimed at the development of a sufficient technology to improve sensory, textural, physical, and microbiological properties of peas snacks (Ps) using solid‐state fermentation (SSF) and submerged fermentation (SMF) with two different lactic acid bacteria (LAB) strains (Lactobacillus casei LUHS210 and Lactobacillus uvarum LUHS245) for 24 hr and ultrasonication (10, 20, and 30 min). To ensure safety of the used technologies, microbiological characteristics and biogenic amines (BAs) content in treated Ps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…A decrease in pH is an indicator of an effective process; however, changes to the fermentable substrate can be caused by many factors, i.e., the technological microorganism's (used for fermentation) characteristics, nutrient source in fermentable media, duration of fermentation, humidity of the substrate, etc. It has been reported that the moisture content of the substrate has a significant influence on pH and, in most cases, lower pH values and higher total titratable acidity were obtained for peas in solid state fermentation conditions ( 38 ). The practice of LAB-based food, as well as feed fermentations, happened accidentally in the beginning, but soon spread due to its many benefits including nutrition, safety and flavor ( 38 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in pH is an indicator of an effective process; however, changes to the fermentable substrate can be caused by many factors, i.e., the technological microorganism's (used for fermentation) characteristics, nutrient source in fermentable media, duration of fermentation, humidity of the substrate, etc. It has been reported that the moisture content of the substrate has a significant influence on pH and, in most cases, lower pH values and higher total titratable acidity were obtained for peas in solid state fermentation conditions ( 38 ). The practice of LAB-based food, as well as feed fermentations, happened accidentally in the beginning, but soon spread due to its many benefits including nutrition, safety and flavor ( 38 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the moisture content of the substrate has a significant influence on pH and, in most cases, lower pH values and higher total titratable acidity were obtained for peas in solid state fermentation conditions ( 38 ). The practice of LAB-based food, as well as feed fermentations, happened accidentally in the beginning, but soon spread due to its many benefits including nutrition, safety and flavor ( 38 , 39 ). Overall, during the fermentation process many compounds are obtained as secondary metabolites of technological microorganisms ( 40 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…The extraction and determination of biogenic amines (BA) in wheat samples followed the procedures developed by Ben-Gigirey et al [ 54 ] with some modifications [ 55 ]. Perchloric acid (0.4 mol/L, 10 mL) containing a known amount of 1.7-diamino-heptane was used for BA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on bovine colostrum -a protein-rich animal product- Bartkiene et al (2018) observed the significant reducing effect of ultrasonication on the tyramine content. Additionally, Gunasekaran et al (2020) reported that ultrasonication has an inactivation effect on lactic acid bacteria, which is the natural microflora of meat (Samelis, 2006). Moreover, the cooking process increased tyramine level in US 60 þ TM, VI 20 þ TM and VI 40 þ TM, probably due to loss of moisture or change in the pH of beef.…”
Section: Effect Of Pretreatment Type and Time On Biogenic Amine Contentmentioning
confidence: 99%